2005
DOI: 10.1007/s10522-005-7953-6
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of p70S6k, GSK-3β, and calcineurin in rat striated muscle during aging

Abstract: In this study we compared the content and phosphorylation levels of several molecules believed to regulate muscle hypertrophy and fiber type changes in the extensor digitorum longus (EDL), soleus, diaphragm, and heart of adult (6 months), aged (30 months), and very aged (36 months) Fischer 344 x Brown Norway rats. With aging, the mass of the EDL and soleus decreased significantly (approximately 38% and approximately 36%, respectively), the diaphragm's mass remained unchanged while the mass of the heart increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 33 publications
1
9
1
2
Order By: Relevance
“…Parkington et al (2004) reported stability of total p70S6K with age in rat PL and tibialis anterior (TA) and increased phosphorylation of p70S6K T389 in TA only. In contrast, Kinnard et al (2005) reported decreased p70S6K and increased p70S6K T389 with age in the rat EDL and soleus. We previously noted decline in total p70S6K and p70S6K 421/424 but no change in p70S6K T389 in the rat biceps brachii with age and stability of all in the rat SG (Rahnert et al, 2011) suggesting difference in p70S6K signaling with age in rat versus macaque tongue muscle.…”
Section: 4 Discussionmentioning
confidence: 72%
“…Parkington et al (2004) reported stability of total p70S6K with age in rat PL and tibialis anterior (TA) and increased phosphorylation of p70S6K T389 in TA only. In contrast, Kinnard et al (2005) reported decreased p70S6K and increased p70S6K T389 with age in the rat EDL and soleus. We previously noted decline in total p70S6K and p70S6K 421/424 but no change in p70S6K T389 in the rat biceps brachii with age and stability of all in the rat SG (Rahnert et al, 2011) suggesting difference in p70S6K signaling with age in rat versus macaque tongue muscle.…”
Section: 4 Discussionmentioning
confidence: 72%
“…Furthermore, GSK-3β activity has been shown to increase in aging and correlate to sarcopenia (Kinnard et al, 2005). Therefore, GSK-3β was measured by Western blot as an indicator of altering catabolic signaling potential during myogenic recovery after disuse.…”
Section: Resultsmentioning
confidence: 99%
“…Studies in skeletal muscles have linked GSK-3b to muscle-wasting conditions. GSK-3b activity has been shown to increase in aged (Kinnard et al, 2005) and burn-injured skeletal muscles (Fang et al, 2007). Inhibition of GSK-3b is required for IGF-1-induced myogenic differentiation (Vyas et al, 2002).…”
Section: Discussionmentioning
confidence: 99%